Studi Hasil dan Kualitas Benih Padi P05 dengan Pemberian Pupuk Hayati (Enterobacter cloacae) - ANESTA, DWI OCKVIAN; NYANA, I DEWA NYOMAN; ASTININGSIH, ANAK AGUNG MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.5, No.2, April 2016, 2016)
The Study Result and the Quality of the Seed Rice P05 by AdministeringBiological Fertilizer (Enterobacter cloacae) The purposes of this research were to find out the influence of biological fertilizer Egary which contains rhizobacteria Enterobacter cloacae related to the crop of P05 rice, as well as to test the effectiveness of biological fertilizer to reduce the utilization of chemical fertilizer, and to obtain the quality of the seed production.The resullt indicated that the augmentation of biological fertilizer plus chemical fertilizer phonska and urea at 100 kg/ha each (Pb) increased the production of the rice crop about 1.0 tons/ha or increased about 38.46% and the result of biological fertilizer plus chemical fertilizer phonska and urea at 200 kg/ha each (Pc) increased about 0,7 tons/ha or about 33.99% if compared with control. The research of Pb treatment with biological fertilizer plus chemical fertilizer phonska and urea at 100 kg/ha each, produced P05 rice crop variety for 7.2 tons/ha and improved the quality of the seeds both physical and physiological parameters, produced 1000 grain weight of seeds, germination and vigor highest power savings and has better endurance than Pc and control (29.62 g, 87.64%, and 81.45%, respectively).
Keywords: Egary of biological fertilizer; Enterobacter cloacae; rice of P05; seed